1987
DOI: 10.1161/01.cir.75.5.1030
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of verapamil in patients with essential hypertension.

Abstract: The cardiovascular effects of intravenous verapamil and 3 months of oral administration of a slow-release form of verapamil (verapamil-SR) were studied in 10 patients with mild-tomoderate essential hypertension. Intravenous verapamil reduced arterial pressure by 15% (p < .01) through a fall in total peripheral resistance of 29% (p < .01); provoked a reflexive rise in heart rate (by 19%, p < .02), cardiac output (by 74%, p < .01), and plasma catecholamines; and shifted intravascular volume toward the cardiopulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(21 citation statements)
references
References 58 publications
0
18
0
3
Order By: Relevance
“…Ver has been shown to have minimal effect on HR when delivered via intracoronary injection. However, intravenous infusion of Ver results in a reflex increase in HR (43). To maintain cardiac output, HR would increase.…”
Section: Discussionmentioning
confidence: 99%
“…Ver has been shown to have minimal effect on HR when delivered via intracoronary injection. However, intravenous infusion of Ver results in a reflex increase in HR (43). To maintain cardiac output, HR would increase.…”
Section: Discussionmentioning
confidence: 99%
“…Como a relação entre a ingestão de sódio e a hipertensão arterial é ainda controversa 20 , e pelo fato de não ter sido feita a avaliação do sódio total alimentar nos indivíduos do grupo de referência, não foram utilizados os dados da ingestão de sódio referentes ao grupo de hipertensos, no presente estudo. Entre as mulheres, o maior índice de massa corporal entre as hipertensas poderia ser um fator a confundir a influência da diferença de ingestão média de cál-cio entre os dois grupos, em relação ao aparecimento de hipertensão arterial 39 . A diferença entre as ingestões médias de cálcio se manteve, mesmo quando corrigidas pelo peso.…”
Section: Discussionunclassified
“…45 Verapamil has also been shown to be superior to a beta-blocker in reduction of LVH without depressing LV function in elderly subjects. 46 In a recently published study, Arrighi et al 47 showed that verapamil enhances LV diastolic filling in normotensive middle-aged and elderly subjects without affecting systolic function.…”
Section: Therapeutic Assumptionsmentioning
confidence: 99%